Modeling and performance analysis of energy harvesting wireless communication systems with reliable energy backup. (4th December 2020) - Tang, Shengda; Tan, Liansheng; Liu, Tao
Summary: Energy harvesting wireless communication system (EH‐WCS) has the capability of harvesting energy for system operations from the surrounding renewable energy sources. However, the randomness and instability of the harvested energy will result in the depletion of the energy consumption. To provide reliable communication services with the quality of service (QoS) guarantee, it is necessary for the EH‐WCS to use a reliable energy backup (REB) for supplying energy to the system during the failure of its primary energy source. In this paper, a novel stochastic model, i.e., the extended Markov fluid flow model, is proposed to describe the EH‐WCS with REB. The Kolmogorov forward equations of the system model are derived. By solving the corresponding equations, we obtain the stationary distributions of the key performance metrics for the EH‐WCS with REB, including the average energy consumption rate of the EH‐WCS, the residual energy distribution, the average energy supply rate by REB, the packet queue length in data buffer, the data queue delay, and the packet blocking probability. A numerical example is provided to investigate the theoretical results, and the effects of the system parameters on the performance are further studied numerically. Both the theoretical insights and the numerical analyses are believed to be important for the design of EH‐WCSs. Abstract : The graphical abstract describes the architecture and working mechanism of an Energy Harvesting Wireless Communication Systems with Reliable Energy Backup (EH‐WCS with REB). An extended Markov fluid flow model is proposed to model this system, some key performance metrics are derived theoretically, and the numerical analyses are given to illustrate the characteristics of the system.